Pengaruh pelatihan, kompensasi, dan kepemimpinan terhadap kepuasan kinerja karyawan di PT PYI - Esa Pertiwi , Dini; Pratminingsih , SA. (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of training, compensation, and leadership on employee performance at PT. PYI partially and simultaneously. This research was conducted with quantitative methods, with the method of selecting samples using simple random sampling. The number of samples in this study were 108 respondents. The data obtained were then processed using multiple linear regression analysis. The results showed that the variables of training, compensation, and leadership had a significant effect on employee performance, either partially or simultaneously. The implication that can be drawn from this research is that companies can improve the performance of their employees by increasing training, providing compensation, and making adjustments to their leadership style.